The Influence of Transformational and Instructional Leadership Styles of School’s Principals on Teacher’s Performance, Motivation, Job Satisfaction and Student Achievement in Primary and Secondary Schools - Andriadi, Dian; Sulistiyo, Urip (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to examine the influence of transformational and instructional leadership styles of school principals on teacher performance, motivation, job satisfaction, and student achievement in primary and secondary schools. A literature review method was employed, synthesizing qualitative and quantitative studies published between 2019 and 2024. The selected studies focus on the relationship between principal leadership styles and key educational outcomes, with data retrieved from sources in both English and Indonesian. The findings highlight that instructional leadership significantly improves teacher performance and job satisfaction by providing structured support and guidance. Transformational leadership fosters motivation, enhances job satisfaction, and promotes student achievement through inspiration and collaboration. The synergy between these leadership styles enhances educational outcomes, with principals effectively balancing both approaches. This review fills a gap by exploring how transformational and instructional leadership styles interact to influence teachers and students, offering a clearer understanding of their complementary roles in various educational contexts. The study provides valuable insights for educators and policymakers by emphasizing the importance of situational leadership and the need for leadership development programs for school principals. Adopting a hybrid approach to leadership can further enhance teacher performance and student achievement.